Bioactive compounds separation with simulated moving bed technology - Santos, Cristiana Areia dos (2018)
Natural products have been progressively forgotten by major pharmaceutical research companies as sources for new drugs in the last half century. Currently one observes a change of strategy, which is promoting a renewed interest on the integration of natural products into pharmaceuticals. Triterpenic acids are a promising group of plant secondary metabolites occurring in cuticular waxes covering fruits, owers, and leaves, providing a wide variety of bene cial biological activities. In this dissertation it was studied the oleanolic and ursolic acids isolation by chromatographic tecnique of simulated moving bed (SMB). The seperation of triterpenic acids is complex due their similar structure. EgiChem laboratory (CICECO, UA) has a SMB unit, but it is necessary to carry out preliminary experiments in order to select the best mobile phase and optimal operating conditions for separation of both acids. For that, it was analyzed the infuence of the solvent/mixture of solvents on the chromatographic separation by measuring selectivity, retention factor and resolution. It was tested a triacontyl column (Acclaim C30), and the best results were obtained with a mobile phase of methanol/ water 95/5 (%, v/v). Then, breakthrough curves have been measured in order to determine process parameters like the equilibrium isotherms (constants Hi) of both oleanolic and ursolic acids, and the global linear driving force (LDF) coe cients of mass transfer (KLDF,i). Data modeling was accomplished using Klinkenberg equation, which is specifcially applicable to linear systems. The equilibrium constants of oleanolic and ursolic acdis were HOA= 2.06 and HUA= 2.16, respectively, and global LDF coe cients were KLDF,OA= 30.48 min-1 and KLDF,UA= 101.45 min-1 with average deviaions of AADROA=18.29 % and AADRUA=26.88 %. Finally the simulation of a SMB unit for a oleanolic/ursolic acids mixture separation was accomplished, with a 2-2-2-2 con guration, using the packing of Acclaim C30 column and methanol/water 95/5 (%, v/v) as mobile phase and the equilibrium and kinetic parameters previously optimized. The obtained results for con guration showed that the separation of oleanolic and ursolic acids is viable, being possible to produce puri ed streams of each acid with concentrations above 99%.